2009
DOI: 10.1073/pnas.0901801106
|View full text |Cite
|
Sign up to set email alerts
|

Transcription coactivator SAYP combines chromatin remodeler Brahma and transcription initiation factor TFIID into a single supercomplex

Abstract: Transcription activation by RNA polymerase II is a complicated process driven by combined, precisely coordinated action of a wide array of coactivator complexes, which carry out chromatin-directed activities and nucleate the assembly of the preinitiation complex on the promoter. Using various techniques, we have shown the existence of a stable coactivator supercomplex consisting of the chromatin-remodeling factor Brahma (SWI/SNF) and the transcription initiation factor TFIID, named BTFly (Brahma and TFIID in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 25 publications
10
71
0
Order By: Relevance
“…Interestingly, both in vivo and in S2 cell, Bap170 is required for stability of Bap180 (Moshkin et al 2007;) and the stability of Bap170, in turn, depends on Sayp (Chalkley et al 2008). The crucial role of Bap170 for PBAP function has also been demonstrated by the recent finding that Bap170 is essential to anchor the PBAP complex to the transcriptional initiator factor TFIID, allowing the formation of the transcriptional supercomplex BTfly (Vorobyeva et al 2009).…”
Section: Resultsmentioning
confidence: 78%
“…Interestingly, both in vivo and in S2 cell, Bap170 is required for stability of Bap180 (Moshkin et al 2007;) and the stability of Bap170, in turn, depends on Sayp (Chalkley et al 2008). The crucial role of Bap170 for PBAP function has also been demonstrated by the recent finding that Bap170 is essential to anchor the PBAP complex to the transcriptional initiator factor TFIID, allowing the formation of the transcriptional supercomplex BTfly (Vorobyeva et al 2009).…”
Section: Resultsmentioning
confidence: 78%
“…The interplay between chromatin remodeling and general transcriptional factors is so close, that these complexes may unite into physically stable formations termed supercomplexes [5]. An example of such cooperation has been demonstrated for the Drosophila SWI/SNF (dSWI/SNF) and TFIID complexes with the SAYP coactivator as a linchpin unit [6].…”
Section: Introductionmentioning
confidence: 99%
“…For one ChIP experiment 3x10 6 of S2 Schneider cells were taken. Crosslinking was made by 15 min incubation with 1,5% formaldehyde and was stopped by addition of 1/20 volume of the 2,5M glycine.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…8 BTFly activates transcription when recruited to the promoters and is functionally indivisible. SAYP is located at multiple sites on the polytene chromosomes of Drosophila larvae, 5,6 indicating that the above mechanism of transcription is apparently widespread. However, no specific activators involved in this mechanism have been identified until recently.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that SAYP acts as a component of stable coactivator supercomplex BTFly, which consists of SAYP, Brahma and TFIID coactivators. 5,6 Brahma is the main chromatin-remodeling enzyme playing a genome-wide role in activation of Pol II-transcribed genes, 7 while TFIID is the key transcription initiation factor for most of Pol II-dependent genes. 8 BTFly activates transcription when recruited to the promoters and is functionally indivisible.…”
Section: Introductionmentioning
confidence: 99%